What determines governments' response time to COVID-19? A cross-country inquiry on the measure restricting internal movements - Elina De Simone; Paulo Reis Mour\~ao (Open Economics, 2021)
After the appearance of the first COVID-19 cases and deaths, countries' responses were enacted at different points in time. This paper explores the factors behind the timeliness of travel restriction policies at the onset of the pandemic. Using instrumental variable techniques on a sample of 149 countries, our empirical exercise shows that while urban population and political stability are conducive to a prompt activation of a government's lockdown policy after initial cases, a country's wealth and the rule of law may produce an opposite effect. When the time from first deaths is considered, the presence of a female leader, net migration levels, voice and accountability, and political stability are associated with a quicker launch of a domestic travel restriction policy, while democracy and a country's wealth may represent an obstacle to an immediate policy activation.
Keywords: 330; Covid-19; institutions; lockdown